(untitled) (Research, Society and Development, 2022)
Syphilis is a Sexually Transmitted Infection (STI) caused by the bacterium Treponema pallidum. The number of cases is growing worldwide, with more than 7 million infected annually. Its main transmission is sexual contact, and pregnant women with the disease can transmit it to their children, generating congenital syphilis. Even with an easily accessible diagnosis and treatment, it remains a disease with a high incidence. The present study seeks to assess the incidence of congenital syphilis in the state of Sergipe from 2012 to 2021, tracing its epidemiological profile and verifying the maternal factors associated with its occurrence. An ecological temporal series, quantitative and descriptive study was carried out with data made available through the Department of Informatics of the Unified Health System (DATASUS), through TABNET in the section of the Notifiable Diseases Information System (SINAN). A progressive growth of cases was observed in the state of Sergipe over the years studied, where the epidemiological profile corresponded to children of mothers with low education, who underwent prenatal care, whose partners mostly did not undergo treatment. Of the total, most patients with congenital syphilis were classified as early, remaining alive without adverse outcomes. With this, there is a need to analyze the factors that influence its increasing rates over the years, because despite public policies to combat the disease, there is still a long way to go for these rates to be controlled.